2016
DOI: 10.1159/000454737
|View full text |Cite
|
Sign up to set email alerts
|

Longer Duration of Sleep and Risk of Cognitive Decline: A Meta-Analysis of Observational Studies

Abstract: Background: Previous observational epidemiological studies have reported inconsistent findings about the association between longer durations of sleep and the risk of cognitive impairment and dementia. To investigate the association between longer durations of sleep and the risk of cognitive decline, we performed a meta-analysis of observational studies. Methods: We searched PubMed, EMBASE, and the bibliographies of relevant articles to retrieve additional studies in July 2015. A total of 53,942 participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
(82 reference statements)
5
13
0
1
Order By: Relevance
“…To our best knowledge, this is the first study simultaneously exploring the independent and combined association of postlunch napping duration and night-time sleep duration on risk of cognitive impairment. Several population-based studies have investigated the independent relationship between night-time sleep duration and cognitive impairment 5 19. We found that longer night-time sleep duration was independently associated with a significantly worse cognitive function (MMSE), in agreement with the majority of previous studies 7 20–22.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our best knowledge, this is the first study simultaneously exploring the independent and combined association of postlunch napping duration and night-time sleep duration on risk of cognitive impairment. Several population-based studies have investigated the independent relationship between night-time sleep duration and cognitive impairment 5 19. We found that longer night-time sleep duration was independently associated with a significantly worse cognitive function (MMSE), in agreement with the majority of previous studies 7 20–22.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, epidemiological data on the association between night-time sleep duration and cognitive impairment is still inconsistent and limited. The majority of studies supported that longer self-reported night-time sleep duration was associated with cognitive impairment 5. On the contrary, some others observed no association 6 7.…”
Section: Introductionmentioning
confidence: 98%
“…However, whether change of sleep duration itself or short sleep duration is the primary cause of higher MCI risk cannot be answered by our study. www.nature.com/scientificreports www.nature.com/scientificreports/ Regarding long sleep duration, several studies showed long sleep to be associated with impaired cognitive performance 13,[40][41][42] . For instance, Ramos et al (2019) 40 found long sleep (> 9 hours) to be predictive for seven-year cognitive decline in episodic learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Негативное влияние нарушений сна на когнитивные функции касается все аспектов этой патологии. Метаанализ обсервационных исследований, опубликованных в PubMed, EMBASE, включивший 53 942 участника (средний возраст 66,9 года), показал, что при большей продолжительности сна относительный риск когнитивного снижения составлял 1,42 (95% ДИ 1,27-1,59) (для УКР 1,38 (95% ДИ 1,23-1,56) и для деменции 1,42 (95% ДИ 1,15-1,77)) [49].…”
Section: сонunclassified